KEEFEKTIFAN MEDIA SMART BOX UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI MENGENAL HURUF - Barokatul Puji Lestari; Saeful Mizan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The ability to recognise letters is one of the basic skills that is very important in the literacy development of primary school children, especially in grade 1. This ability is one of the main foundations for students in developing reading and writing skills in the next stage. This study aims to analyse the effectiveness of the Smart Box media in improving students' learning outcomes in letter recognition. The study was conducted using a descriptive quantitative approach with 18 first-grade students at UPT SDN Rayun 2 as the research subjects. Data collection was conducted through pre-test and post-test evaluations. The effectiveness analysis used the N-Gain formula to measure changes in students' understanding before and after using the media. This aligns with the 100% pass rate of students in the post-test. Based on the N-Gain analysis, the effectiveness level was found to be high for all students. This indicates that the Smart Box media falls into the ‘effective’ category for supporting learning in primary schools.